Minmax fractional programming problem involving generalized convex functions - Jayswal, Anurag; Stancu-Minasian, I.M.; Kumar, Dilip (Rev. Anal. Numér. Théor. Approx., 2012)
In the present study we focus our attention on a minmax fractional programming problem and its second order dual problem. Duality results are obtained for the considered dual problem under the assumptions of second order \(\left( {F,α ,ρ ,d}\right) \) -type I functions.